2001
DOI: 10.1097/00006982-200110000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Biomicroscopy of Sclerotomy Sites

Abstract: Vitreous shaving of sclerotomy sites using depressed vitrectomy significantly reduces vitreous incarceration. This may reduce the rate of sclerotomy-related complications following PPV in selected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The residual vitreous strand surrounding the cannula can clog the ports and can lead to increased rates of complications such as fibrovascular proliferation, recurrent vitreous hemorrhage and retinal breaks leading to detachment [17]. Therefore, many studies were undertaken to determine the effect of the scleral incision shape on the complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…The residual vitreous strand surrounding the cannula can clog the ports and can lead to increased rates of complications such as fibrovascular proliferation, recurrent vitreous hemorrhage and retinal breaks leading to detachment [17]. Therefore, many studies were undertaken to determine the effect of the scleral incision shape on the complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…It would be much more difficult to observe these areas in case of vitreous hemorrhage, vitreous opacity, or opaque vitreous skirt [6]. Although ultrasound biomicroscopy (UBM) have been used for detecting the inner aspect of sclerotomy sites before surgery [12, 13], by which the degree of vitreous incarceration could be graded indirectly [13, 14]. However, UBM could not identify different tissues incarcerated in sclerotomy sites due to the same echo of retina and vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…Vitreous shaving around sclerotomy sites has been found to reduce vitreous incarceration following pars plana vitrectomy. 10 A study in patients evaluating the sclerotomy site endoscopically through another cannula in 32 eyes that underwent 23-gauge non-valved cannula vitrectomy found no vitreous incarceration in 30 eyes (94%) when one cannula was removed with insertion of a light probe, with only minimal vitreous incarceration observed in the other two eyes. 11 Experimental models in porcine cadaver eyes showed that interposing a light probe through the cannula during its removal reduced the rate and severity of vitreous incarceration.…”
Section: Introductionmentioning
confidence: 99%